IMPLEMENTASI AGILE DEVELOPMENT BERBASIS WEB BASED PADA SISTEM INVENTORY - Akwilla, Hiskia; Jollyta, Deny (Jurnal Manajamen Informatika Jayakarta, 2024)
The inventory management at the Aeng store causes errors in the recognition of revenue and inventory calculation, making process inefficient and incurring losses. The purpose of this research is to analyze the needs required by Aeng Stores as well as design the application of the inventory system of good that can facilitate in carrying out the recording of sales and purchase reports, recording inventory reports, and recording supplier data. The test method used is the Black Box, which tests the software based on its external appearance and functionality, not the source code of the program. The results of this study show that applying Agile Development Method to inventory management brings many benefits. These include making inventory management processes more efficient, improving inventory accuracy, reducing excessive costs, and increasing responsiveness in a rapidly changing business environment. The conclusions derived from the tests that have been carried out, using Agile Development Method can be a fairly effective and efficient way for the Aeng Store to manage store inventory.